Cemetery girl. Book three, Haunted - Harris, Charlaine; Golden, Christopher (Harris, Charlaine. Cemetery girl ;, 2018)
With a mysterious investigator and hardened killers on her trail, Calexa's true identity is about to be revealed, but will she live long enough to learn her real name?--Page 4 of cover.